Натуризм ба түүний хоёр гол урсгалын тухай - Д. Галбаатар (Acta Mongolica, 2013)
The ancient and modern literature of Mongolia has created many diflerent genres, akin to the famous literary pieces that have spawned across the globe. One of these genres is Naturalism, which is an important feature of Mongolia literature.